KORELASI ANTARA STATUS GIZI ANEMIA DENGAN BERAT BADAN DAN PANJANG BADAN BAYI BARU LAHIR - Ema Wahyuningrum (Universitas Harapan Bangsa Purwokerto, 2017)
Nutritional status during pregnancy will affect the nutritional status of newborns. Anemia and in pregnancy can affect the growth and development of the fetus during pregnancy and thereafter such as LBW, stunting at infants and toddlers. RSUD dr. R. Goeteng Taroenadibrata as Referral Hospital from Puskesmas inside and outside Purbalingga. The aim of this research is to know the relationship of nutritional status during pregnancy to the weight and length of newborn. Analytic survey research design with cross sectional approach. Sampling technique using puposive sampling, sample of pregnant woman's research is not anemia 20 people and anemia 20 people. Univariate data analysis was in the form of frequency distribution, bivariate analysis in the form of chi square and strength of relationship seen from OR parameter. The result of the research showed that there was correlation between anemia pregnant mother with newborn's body length (p = 0,022) and newborn weight (p = 0,001 ). Anemic pregnant women have 4.8 chances of having a short body length compared to mothers not anemic. Anemic pregnant women have a 9.3 times chance of having LBW compared to mothers not anemic. The health worker handles pregnancy with anemia as early as possible to prevent the growth and development of the fetus. Keywords: Nutritional Status of anemia, birth weight, baby's length